Study of Laminated Veneer Lumber (LVL) Sengon to Concrete Joint Using Two-Dimensional Numerical Simulation - Urwatul Wusqo; Ali Awaludin; Angga Fajar Setiawan; Inggar Septhia Irawati (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
The connection system is a critical part of Timber – Concrete Composite (TCC) floor structures. The behaviour of the connection needs to be known to predict the behaviour of composite structure accurately. Screws are one kind of connector that mostly used in the composite structure due to its installation ease and high withdrawal strength. This study carried out a two-dimensional numerical simulation to examine the behaviour of LVL Sengon-concrete joint using OpenSees software. The lag screw used to connect LVL Sengon and concrete. In this simulation, the screw was assumed as a beam with hinges element that supported by a set of springs representing the strength of LVL Sengon and concrete. Some input parameters for this simulation were obtained from the material test and previous research. The effect of secondary axial force was considered into the load-displacement curve resulted from the numerical simulation. This study performed several simulations towards the variation of the screw diameter, penetration depth, and concrete compressive strength. The capacity of the connections resulted from the numerical simulation were overestimates the manual calculation using EYM theory and NDS 2018 equations. The capacity of the connection increased about 146% to 284% due to the addition of secondary axial forces. In addition, this simulation can adequately predict the shear force, bending moment, and deformation of the screw. There is a plastic hinge formed in the screw after the screw being deformed a quite large. It shows the same yield mode with the manual calculation using EYM theory and NDS 2018 equations. This simulation also can show the contribution of each spring elements to resist the load until its ultimate strength.